Antioxidant Bio-Compounds from Chestnut Waste: A Value-Adding and Food Sustainability Strategy - Roberta Barletta; Alfonso Trezza; Andrea Bernini; Lia Millucci; Michela Geminiani; Annalisa Santucci (Foods)
In an era of escalating environmental challenges, converting organic residues into high-value bioactive compounds provides a sustainable way to reduce waste and enhance resource efficiency. This study explores the potential of the circular bioeconomy through the valorization of agricultural byproducts, with a focus on the antioxidant properties of specific chestnut burr cultivars. Currently, over one-third of food production is wasted, contributing to both humanitarian and environmental crises. Through circular bioeconomy, we can transform biological waste into valuable products for use in fields like food innovation and sustainability. The antioxidant effects of three chestnut cultivars, Bastarda Rossa, Cecio, and Marroni, were assessed through in vitro assays, highlighting their potential to combat oxidative stress—an important factor for health-related applications. The characterization of the three cultivars showed the major presence of ellagic acid and gallic acid in the extract, renowned for their antioxidant activity. In vitro assays evaluated the phenolic and flavonoid content, as well as the antioxidant activity of the three extracts, confirming the cultivar Cecio as the richest in these bioactive compounds and the most performative in antioxidant assays. In vitro antioxidant and oxidative stress recovery assays on SaOS-2, fibroblast, and chondrocyte cell lines displayed a strong antioxidant activity. Furthermore, the cytotoxicity assay demonstrated the safety of all three extracts in the tested human cell lines. In silico docking simulations further validated the biological relevance of these compounds by predicting strong hydrophobic and polar interactions with oxidative stress-related protein targets. Overall, this study demonstrates the antioxidant properties of chestnut byproducts. The findings contribute to the development of functional foods, nutraceuticals, and other applications, underscoring the role of chestnut cultivars in advancing circular bioeconomy practices.